Factors Affecting User Satisfaction and Benefits of SIMRS at the Regional General Hospital Beriman - et. al., Lis Indrayati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The application of the Hospital Management Information System (SIMRS) is very important to achieve quality health services. This study aims to determine the factors that affect the acceptance of SIMRS implementation. The research was conducted using the Human, Organization, Technology - Fit (HOT-Fit) method. This research is a quantitative study using an analytic survey design with a cross sectional study approach. The research was conducted at Regional General Hospital (RSUD) Beriman Balikpapan from March to April 2021 with 145 respondents who were SIMRS users. Data analysis was performed using path analysis. The results showed that the system quality variable had no effect on user satisfaction with a significance value of 0.844 (p> 0.05). There is a variable effect of information quality on user satisfaction with a significance value of 0.000 (p <0.05). There is a variable effect of service quality on user satisfaction with a significance value of 0.000 (p <0.05). There is an effect of user satisfaction on benefits with a significance value of 0.033 (p <0.05). This study shows that there is an effect of information quality and service quality on user satisfaction, while system quality has no significant effect on user satisfaction. For this reason, recommendations are needed to make system improvements, especially related to existing functions in the system, improvements to data accuracy and compatibility between system functions and the needs of system users.